In Search of the Regulatory Optimum for Digital Platforms: A Comparative Analysis - Koshel, Alexey; Kuzminov, Yaroslav; Kruchinskaia, Ekaterina; Lesiv, Bogdan (Legal Issues in the Digital Age, 2025)
The rapid growth of digital platforms and ecosystems has become a significant economic phenomenon on a global scale. This growth is due to the ability of these platforms to provide additional and flexible opportunities that are mutually beneficial for sellers, buyers, and platform workers. Because of it the activities of digital platforms have a positive impact on the overall gross domestic product of countries worldwide. The focus of the study is made on the regulatory frameworks for digital platforms both in Russia and around the world, including the rights and obligations of owners, operators, and users resulting from their participation in market transactions. The study does not include digital platforms used in the public sector or social media and messaging services. Scholar methods: comparative legal, formal logic, formal doctrinal, historical legal, as well as analytical, synthetic, and hermeneutical methods are systematically and integrally applied in the research. Based on the sources material, a hypothesis has been proposed regarding three stages of platform regulation growth globally and in Russia. Upon the results of an analysis of the three-stage evolutionary process of legal regulation for e-commerce, it has been found that there is commonly inconsistent impact of various branches of law on the different areas of social relations or different types of platforms. Among this inconsistency are legal gaps and conflicts of legal rules, which make benefits for stakeholders spontaneous rather than the result of systematic interaction within the regulatory framework. Authors of the article identify a major source of legal uncertainty: the absence of standardized terms and harmonized regulatory principles that account for the unique nature of cross-industry digital economy. Lessons from global jurisdictions and three stages of e-commerce regulation reveal that, in its latest phase, the platform economy necessitates system of tailored legal definitions to manage its multifaceted activities. The survey proposes such conceptual structures that may be employed in Russian legal system. They reflect the multidimensional nuances of civil, tax, competition, information, and administrative laws. Additionally, a balanced scheme of general principles has been developed that would ensure the transparent interaction of digital platforms with society, the state, and economic entities.